Changing the Mechanism for CO2 Hydrogenation Using Solvent‐Dependent Thermodynamics. Issue 47 (23rd October 2017) - Burgess, Samantha A.; Appel, Aaron M.; Linehan, John C.; Wiedner, Eric S.
Abstract: A critical scientific challenge for utilization of CO2 is the development of catalyst systems that function in water and use inexpensive and environmentally friendly reagents. We have used thermodynamic insights to predict and demonstrate that the HCo I (dmpe)2 catalyst system, previously described for use in organic solvents, can hydrogenate CO2 to formate in water with bicarbonate as the only added reagent. Replacing tetrahydrofuran as the solvent with water changes the mechanism for catalysis by altering the thermodynamics for hydride transfer to CO2 from a key dihydride intermediate. The need for a strong organic base was eliminated by performing catalysis in water owing to the change in mechanism. These studies demonstrate that the solvent plays a pivotal role in determining the reaction thermodynamics and thereby catalytic mechanism and activity. Abstract : Charting a new path : Switching from organic solvent to water alters the mechanism of catalytic CO2 hydrogenation by a cobalt phosphine complex. The mechanism change is attributed to the favorable impact of water on the hydride donor ability of a key catalytic intermediate. Kinetic studies indicate that this catalyst is among the most active base‐metal catalysts for CO2 hydrogenation in water.